1978
DOI: 10.1159/000148928
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Defective Measles Virus from Brain Biopsies of Three Patients in Iran with Subacute Sclerosing Panencephalitis

Abstract: Three cytopathic strains of subacute sclerosing panencephalitis (SSPE) virus were isolated from brain biopsies of three patients. These strains were isolated and maintained by cocultivation of infected brain cells with fresh Vero cells. The biological characteristics of two strains were studied. It was found that these strains remain cell-associated after repeated cocultivations with Vero cells and produce plaques under fluid medium or traga-canth overlay. The correlation with measles virus was demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…More detailed examinations on antibody responses at structural protein levels in natural measles is required. All the three strains of SSPE virus used in the present study are highly cellassociated and show high neurovirulence in rodents and monkeys (Yamanouchi et al, 1976;Mirchamsy et al, 1978). The present study disclosed a significant difference in biological properties; Niigata-1 strain did not release cell-free virus and was negative in hemadsorption under either standard or high-salt condition, whereas ZH and SI strains were found to release a small amount of cell-free virus and to be hemadsorption-positive under both the conditions (Table II).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…More detailed examinations on antibody responses at structural protein levels in natural measles is required. All the three strains of SSPE virus used in the present study are highly cellassociated and show high neurovirulence in rodents and monkeys (Yamanouchi et al, 1976;Mirchamsy et al, 1978). The present study disclosed a significant difference in biological properties; Niigata-1 strain did not release cell-free virus and was negative in hemadsorption under either standard or high-salt condition, whereas ZH and SI strains were found to release a small amount of cell-free virus and to be hemadsorption-positive under both the conditions (Table II).…”
Section: Discussionmentioning
confidence: 98%
“…SSPE virus, such as cell-associated Niigata-1 (Doi et al, 1972), ZH and SI (Mirchamsy et al, 1978) strains were grown by cocultivation with Vero cells. SSPE virus-infected Vero cells were maintained in Eagle's minimum essential medium (EMEM) supplemented with 5% calf serum, 0.11% sodium bicarbonate, 100 units of penicillin and 100 pg per ml of streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Woelk et al identified several positiveselection amino acid sites in the SSPE strain (67), but S546G was absent from the list. It is possible that the S546G substitution was introduced into the SI strain genome during the propagation in Vero cells but not in the brain, since the SI strain was isolated using Vero cells (29). Vero cells are 100 to 1,000 times less sensitive than SLAM-positive B95a cells for the isolation of wt MV strains (22,34), and wt MV strains readily adapt to use CD46 after several passages in Vero cells (69).…”
Section: Discussionmentioning
confidence: 99%
“…The SI strain was isolated in 1976 from a patient with SSPE by cultivating brain tissue biopsy samples with Vero cells (29). The patient was 8 years of age and had suffered from acute measles at 4 years of age (29).…”
mentioning
confidence: 99%
See 1 more Smart Citation